Enhancing qualitative characteristics of useful financial information: slant from Malaysian Companies Act 2016 / Muslimah Mohd Jamil - Mohd Jamil, Muslimah (Faculty of Accountancy, 2021)
In Malaysia, registered companies, either public or private, need to follow the Companies Act 2016 (the Act), published by the government of Malaysia. In order to prepare the financial statement, the company is required to follow the Malaysian Financial Reporting Standard (MFRS), published by the Malaysian Accounting Standard Board (MASB). A different organisation is publishing these two standards, and it has been seen as a separate standard and does not link to one another. Thus, this article aims to explain four enhancing qualitative characteristics of useful financial information from the point of view of the Act.